2020
DOI: 10.3389/fimmu.2020.00958
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Promotes the Activation of Fibroblast-Like Synoviocytes From Patients With Rheumatoid Arthritis

Abstract: Objective: To evaluate the biological effect and mechanisms of C-reactive protein (CRP) on the activation of fibroblast-like synoviocytes (FLSs) from patients with rheumatoid arthritis (RA). Study design: To understand if CRP is involved in RA, expression of CRP and its receptors CD32/64 was examined in synovial tissues from RA patients and normal controls. In vitro, the potential role and mechanisms of CRP in FLS proliferation and invasion, expression of pro-inflammatory cytokines, and activation of signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In addition, liver-targeted CRP siRNA, which decreased CRP expression in hepatocytes, exerted an effect similar to that of anti-CRP antibodies in Liang's study [25]. Additionally, CRP signalling was highly active in the synoviocytes from RA patients, and the addition of exogenous CRP could induce synovial in ammation by activating NF-κB signalling [32]. Some researchers attributed these phenomena to intervention at different stages of RA and suggested that CRP may play a protective role during the early stage of RA but exert detrimental effects during active RA [25,28].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, liver-targeted CRP siRNA, which decreased CRP expression in hepatocytes, exerted an effect similar to that of anti-CRP antibodies in Liang's study [25]. Additionally, CRP signalling was highly active in the synoviocytes from RA patients, and the addition of exogenous CRP could induce synovial in ammation by activating NF-κB signalling [32]. Some researchers attributed these phenomena to intervention at different stages of RA and suggested that CRP may play a protective role during the early stage of RA but exert detrimental effects during active RA [25,28].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, liver-targeted CRP siRNA, which decreased CRP expression in hepatocytes, exerted an effect similar to that of anti-CRP antibodies in Liang's study [25]. Additionally, CRP signalling was highly active in the synoviocytes from RA patients, and the addition of exogenous CRP could induce synovial in ammation by activating NF-κB signalling [32]. Some researchers attributed these phenomena to intervention at different stages of RA and suggested that CRP may play a protective role during the early stage of RA but exert detrimental effects during active RA [25,28].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, liver-targeted CRP siRNA, which decreased CRP expression in hepatocytes, exerted an effect similar to that of anti-CRP antibodies in Liang et al's study [ 25 ]. Additionally, CRP signalling was highly active in the synoviocytes from RA patients, and the addition of exogenous CRP could induce synovial inflammation by activating NF- κ B signalling [ 32 ].…”
Section: Discussionmentioning
confidence: 99%